2000
DOI: 10.1016/s0022-5347(05)67875-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Microtubule-Active Drugs Followed by Ketoconazole in Human Metastatic Prostate Cancer Cell Lines

Abstract: Pulse-administration of vinblastine followed by continuous administration of ketoconazole warrants investigation in the treatment of hormone-independent metastatic prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…The second pharmaceutical is Ketoconazol, a general cytochrome P450 inhibitor that is usually used in second-line androgen-deprivation therapy (35,36). The rationale behind its use is that it inhibits the P450s involved in androgen synthesis and results in a more complete androgen ablation (37).…”
Section: Discussionmentioning
confidence: 99%
“…The second pharmaceutical is Ketoconazol, a general cytochrome P450 inhibitor that is usually used in second-line androgen-deprivation therapy (35,36). The rationale behind its use is that it inhibits the P450s involved in androgen synthesis and results in a more complete androgen ablation (37).…”
Section: Discussionmentioning
confidence: 99%
“…33,52 High-content profiling was used here to dissect the interaction of the classical antifungal drug ketoconazole with 2 microtubule drugs against 3 target activities within 2 cell types. This rapid combinatorial approach led to the Figure 8 was expanded to the microplate level using the following approach: (1) the cellular data were divided into quadrants as shown in Figure 8, (2) the number of cells in quadrant II (cells with relatively highly phosphorylated 90 kDa ribosomal s6 kinase [RSK90] accompanied by stabilized or aggregated microtubules) was divided by the number of cells in quadrant III (cells with RSK90 phosphorylation and microtubule stability at or near control levels), and (3) these population ratio values were plotted as a function of drug concentration as color-coded dots with ratio values increasing on the yaxis, similar to a standard bar graph representation.…”
Section: Dissecting the Complex Interplay Of Cells Targets And Intementioning
confidence: 99%
“…Work done previously with PC-3 cells showed that ketoconazole had little or no potentiating effect when combined with paclitaxel or vinblastine. 33 It is interesting to note that high-content profiling revealed that ketoconazole was stronger in potentiating microtubule drug activity in cervical adenocarcinoma cells (HeLa) than in prostate adenocarcinoma cells (PC-3), despite the fact that ketoconazole has become associated with the treatment of prostate cancer. These results underscore the need to understand the full range of cellular processes that ketoconazole influences and how it can be advantageously combined with other drugs to potentially minimize side effects while maximizing efficacy.…”
Section: Dissecting the Complex Interplay Of Cells Targets And Intementioning
confidence: 99%
See 1 more Smart Citation
“…However, increased biological activity of calcitriol may not be selective for anti-proliferative effects but may also include hypercalcemia. Ketoconazole, the most readily available imidazole derivative that inhibits mammalian P450 enzymes [117], exhibits growth inhibitory activity by itself in PCa cells [306] as well as in primary prostatic epithelial cells [118]. Ketoconazole enhances the inhibitory effects of calcitriol on the growth of PC-3 cells in culture as well as their growth as xenografts in nude mice [120].…”
Section: -Hydroxylase Inhibitorsmentioning
confidence: 99%